Van der Waals sheets for rechargeable metal-ion batteries - David, Lamuel Abraham (Kansas State University, 2015)
The inevitable depletion of fossil fuels and related environmental issues has led to exploration of alternative energy sources and storage technologies. Among various energy storage technologies, rechargeable metal-ion batteries (MIB) are at the forefront. One dominant factor affecting the performance of MIB is the choice of electrode material. This thesis reports synthesis of paper like electrodes composed for three representative layered materials (van der Waals sheets) namely reduced graphene oxide (rGO), molybdenum disulfide (MoS₂) and hexagonal boron nitride (BN) and their use as a flexible negative electrode for Li and Na-ion batteries. Additionally, layered or sandwiched structures of vdW sheets with precursor-derived ceramics (PDCs) were explored as high C-rate electrode materials. Electrochemical performance of rGO paper electrodes depended upon its reduction temperature, with maximum Li charge capacity of 325 mAh.g⁻¹ observed for specimen annealed at 900°C. However, a sharp decline in Na charge capacity was noted for rGO annealed above 500 °C. More importantly, annealing of GO in NH₃ at 500 °C showed negligible cyclability for Na-ions while there was improvement in electrode's Li-ion cycling performance. This is due to increased level of ordering in graphene sheets and decreased interlayer spacing with increasing annealing temperatures in Ar or reduction at moderate temperatures in NH₃. Further enhancement in rGO electrodes was achieved by interfacing exfoliated MoS₂ with rGO in 8:2 wt. ratios. Such papers showed good Na cycling ability with charge capacity of approx. 225.mAh.g⁻¹ and coulombic efficiency reaching 99%. Composite paper electrode of rGO and silicon oxycarbide SiOC (a type of PDC) was tested as high power-high energy anode material. Owing to this unique structure, the SiOC/rGO composite electrode exhibited stable Li-ion charge capacity of 543.mAh.g⁻¹ at 2400 mA.g⁻¹ with nearly 100% average cycling efficiency. Further, mechanical characterization of composite papers revealed difference in fracture mechanism between rGO and 60SiOC composite freestanding paper. This work demonstrates the first high power density silicon based PDC/rGO composite with high cyclic stability. Composite paper electrodes of exfoliated MoS₂ sheets and silicon carbonitride (another type of PDC material) were prepared by chemical interfacing of MoS₂ with polysilazane followed by pyrolysis . Microscopic and spectroscopic techniques confirmed ceramization of polymer to ceramic phase on surfaces on MoS₂. The electrode showed classical three-phase behavior characteristics of a conversion reaction. Excellent C-rate performance and Li capacity of 530 mAh.g⁻¹ which is approximately 3 times higher than bulk MoS₂ was observed. Composite papers of BN sheets with SiCN (SiCN/BN) showed improved electrical conductivity, high-temperature oxidation resistance (at 1000 °C), and high electrochemical activity (~517 mAh g⁻¹ at 100 mA g⁻¹) toward Li-ions generally not observed in SiCN or B-doped SiCN. Chemical characterization of the composite suggests increased free-carbon content in the SiCN phase, which may have exceeded the percolation limit, leading to the improved conductivity and Li-reversible capacity. The novel approach to synthesis of van der Waals sheets and its PDC composites along with battery cyclic performance testing offers a starting point to further explore the cyclic performance of other van der Waals sheets functionalized with various other PDC chemistries.
Keywords: Graphene; Battery; Sodium ion; MoS₂; Lithium ion; Polymer derived ceramic